‘On the ship there were more people fleeing like me’: diasporic itineraries from West Africa in Latin America - Roa Ortega, Pedro (2022)
Drawn upon ethnographical interviews, this essay is a brief case study on the contemporary West African transnational human mobility flows toward Mexico’s northern border. First, the article presents a generalpanorama on one determining rationale: institutionalized sociopolitical violence. After, the text reflects on the main features of the Latin Americanroute: its inconsistencies and ambiguities. From a diasporic perspective, the paper emphasizes the transnational networks and relations enabling thesetransatlantic-intercontinental itineraries despite pervasive global border securitization regimes.